Análise do desenvolvimento de conceitos científicos sobre a teoria da evolução das espécies em alunos do ensino médio - Silva, Douglas Verrangia Corrêa da (2004)
In this investigation we have analyzed the development of scientific concepts of students engaged in a teaching intervention on the theme Evolution of the species . That activity had as main characteristics: a) its structure was formulated in a way that aimed on stimulating students reasoning and interfering in one s conception on the theme; b) it was also supported by a teaching instrument that was elaborated with the purpose of simulating the evolutionary process and create a proper environment to develop the intended activities. This intervention, in which the researcher acted as the teacher and students of a University s exam preparatory course participated as volunteers, was meant to generate a diagnosis on the ideas of the participants and also interfere and evaluate (at the end of the process) those. For such, the intervention was subdivided in three phases: Diagnostic Evaluation, Development and Evaluation of the Learning Process. In order to make the investigation possible, a series of data were collected. The concerned: i) the ideas and concepts of the students; ii) the conditions of the learning available to them; iii) teachers interventions; iv) teacher-student interactions; v) different ways of utilizing the teaching instrument. Having in mind the objective of this research, as said before, the same kinds of data were gathered in all phases of the intervention and were subject of analysis regarding each phase and the whole process. As a result of the research we were able to characterize the conceptual development of the participants along the process. One could observe that there was development of elements of the scientific concepts, but the development of a system of meanings, consisting on genuine scientific meanings, that had just began. This partial development enabled us to highlight the importance of the cognitive work of systematization and application of concepts, in order that the process of learning scientific concepts happens through a acquisition of a system of meanings consisting on concepts with a high level of conscience and generalization. We were able to conclude that the consideration of Vygotski s theory on the teaching practice related to science concepts can offer a huge advancement in a significant learning of these concepts. We also identified the important role of the reasoning and actions of the teacher along the process, including his knowledge on the students ideas, on their learning process. In addiction, we have some conclusions about the teaching instrument role in the intervention: was positive in generating motivation on participating in many of the activities done during the intervention; had a positive role in the diagnosis of the students ideas; it helped establishing rules about the use of the instrument when regarding the discussions and situations that were good for the learning process, but it related to some learning difficulties presented by the students; it collaborated in proposing e developing activities that articulated scientific concepts and thought operations ; was possible to allow the central role of the conduction, by the teacher, of the activities related to the instrument to characterize the activity.